ANALYSIS OF FACTORS OF COMPANY VALUE (CASE STUDY ON MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN 2017-2020) - Adhi Widyakto; Yohanes Suhardjo; Windasari Rachmawati (Universitas Tidar, 2022)
This research aims to test the influence of profitability, liquidity, leverage on Price Book Value. in manufacturing companies listed on the Indonesia Stock Exchange in 2017 and 2020. This type of research is quantitative. The population in this study 284 is a manufacturing company listed on the Indonesia Stock Exchange in 2017 and 2020. The samples in this study used purposive sampling methods and were obtained by 200 manifacturing companies that fit the predetermined criteria. The data analysis technique used is multiple regression analysis with the SPSS 24.0 program. The results showed that the variable Return On Equity, Current Ratio, Debt Equity Ratio, Sales Growth had a Significant Positive Effect on PBV studies in Manufacturing Companies in 2017-2020.